Pengaruh Dana Pihak Ketiga (DPK), Capital Adequancy Ratio (CAR), Loan To Deposit Ratio (LDR), Return On Asset (ROA), Terhadap Penyaluran Kredit - Novi Sriwahyuni; Hesty Ervianni Zulaecha; Imam Hidayat; Ahmad Jayanih (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study is to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Return On Assets (ROA) on credit at registered National Private Commercial Banks in 2015-2020 on the Indonesia Stock Exchange (IDX). The research time period used is 6 years, namely the 2016-2020 period. The population in this study are National Private Commercial Bank companies listed on the Indonesia Stock Exchange during the 2015-2020 period. The total samples tested were 11 companies selected by purposive sampling technique so that the data analyzed amounted to 66 companies. The data analysis technique uses panel data regression with the help of the Eviews 9.0 program. The results of this study indicate that Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Return On Assets (ROA) are equally influential positive and significant to Credit Disbursement.